FINANCIAL MANAGEMENT TRAINING IN SMALL INDUSTRIES - Nursyirwan, Vivi Iswanti (Jurnal Abdimas, 2020)
Community Service (PKM) is a form of Tri Dharma college activity.As an academic, the lecturer of accounting study Program S1 of Pamulang University strives to implement Tri Dharma colleges by organizing community service activities (PKM).The implementation of community service lasts for 3 days. The purpose of this community devotion is to provide understanding to the individual/small and medium entrepreneurs in the South Tangerang community Berkibar about practical and simple knowledge of management of financial management In accordance with the principles of financial management.The method of study used is a classical method with discussion/question and simulation approach with the intent that the material can be received by the participants well.Guidance/consultation is done either through one last meeting session with the participant, or over the phone.The results of this dedication demonstrate with the training that participants have the knowledge and insight as a small businessman who manages to manage the finances and also able to seek opportunities and sustainable knowledge.Keywords: management; financial; small and medium industries